2005
DOI: 10.1080/10615800500289524
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment, posttraumatic growth and negative emotions among former political prisoners

Abstract: Although traumatic events are generally associated with negative psychosocial consequences, trauma survivors also report positive changes in themselves, human relationships and spirituality. Our aims are, first to study associations between exposure to torture and ill-treatment and posttraumatic growth and negative emotions, and second, to examine the role of adult attachment in moderating the association between exposure and positive growth. The participants were 275 Palestinian men imprisoned in a political … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
68
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 47 publications
(53 reference statements)
11
68
2
4
Order By: Relevance
“…Indeed, there is evidence in support of this proposal. Salo et al (2005) found positive associations between secure attachment and perceived PTG, in particular for the personal strength, affiliation to others, and spiritual change subscales of the Posttraumatic Growth Inventory (PTGI; Tedeschi & Calhoun, 1996). However, the evidence for a relationship between secure attachment and PTG is not consistent.…”
Section: Posttraumatic Growth (Ptg)mentioning
confidence: 77%
See 1 more Smart Citation
“…Indeed, there is evidence in support of this proposal. Salo et al (2005) found positive associations between secure attachment and perceived PTG, in particular for the personal strength, affiliation to others, and spiritual change subscales of the Posttraumatic Growth Inventory (PTGI; Tedeschi & Calhoun, 1996). However, the evidence for a relationship between secure attachment and PTG is not consistent.…”
Section: Posttraumatic Growth (Ptg)mentioning
confidence: 77%
“…Attachment anxiety was a unique predictor of posttraumatic stress and trauma-related psychological problems in several studies (Besser & Neria, 2010; 2012; Besser, Neria, & Haynes, 2009;Salo, Qouta, & Punamaki, 2005), whereas avoidant attachment was associated with PTS in only one study (O'Connor & Elklit, 2008). One study collapsed anxiety and avoidance into a general category of insecure attachment and found a positive association between insecure attachment and PTS (Ghafoori, Hierholzer, Howsepian, & Boardman, 2008).…”
Section: Attachment Patterns and Posttraumatic Stress Symptomsmentioning
confidence: 99%
“…war) and to experience positive changes (in Israeli undergraduates (Mikulincer et al,2006) and political prisoners (Salo et al, 2005). Another study reported a negative association between attachment-avoidance and perceived PTG in a sample composed of university staff and students (Gizem Arikan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Clough u. Cloitre 2006) Salo et al (2005). haben in einer Stichprobe traumatisierter politischer Gefangener beschrieben, dass die Bindungssicherheit insbesondere im Zusammenhang mit schweren Traumatisierungen die Entwicklung positiver Beziehungen zu anderen fördert und die Prä-valenz negativer Emotionen mindert, also einen wichtigen Schutzfaktor darstellt.…”
unclassified